Does Aerobic Exercise Mitigate the Effects of Cigarette Smoking on Arterial Stiffness?. Issue 9 (18th August 2014) - Park, Wonil; Miyachi, Motohiko; Tanaka, Hirofumi
<x xml:space="preserve">Abstract</x> The largest percentage of mortality from tobacco smoking is cardiovascular‐related. It is not known whether regular participation in exercise mitigates the adverse influence of smoking on vasculature. Accordingly, the authors determined whether regular aerobic exercise is associated with reduced arterial stiffness in men who smoke cigarettes. Using a cross‐sectional study design, 78 young men were studied, including sedentary nonsmokers (n=20), sedentary smokers (n=12), physically active nonsmokers (n=21), and physically active smokers (n=25). Arterial stiffness was assessed by brachial‐ankle pulse wave velocity (baPWV). There were no group differences in height, body fat, and systolic and diastolic blood pressure. As expected, both physically active groups demonstrated greater maximal oxygen consumption and lower heart rate at rest than their sedentary peers. The sedentary smokers demonstrated greater baPWV than the sedentary nonsmokers (11.8±1 m/s vs 10.6±1 m/s, P=.036). baPWV values were not different between the physically active nonsmokers and the physically active smokers (10.8±1 m/s vs 10.7±1 m/s). Chronic smoking is associated with arterial stiffening in sedentary men but a significant smoking‐induced increase in arterial stiffness was not observed in physically active adults. These results are consistent with the idea that regular participation in physical activity may mitigate the adverse effects of smoking on the vasculature.